Strengthening the Cadre and Recruitment Function of Political Parties in the General Elections in the Democratic State of Indonesia - Widayati, ‎; Winanto, ‎; Huda, Moh. Nurul (KnE Social Sciences, 2025)
One of the functions of political parties is to conduct political recruitment to prepare prospective leaders who are chosen through general elections and regional head elections. Candidates proposed by political parties often come from outside the party. This happens because political cadreship and recruitment do not run well. The problem discussed is the process of cadre formation by political parties in facing elections and the process of political party recruitment in general elections in the democratic country of Indonesia. The research method used is normative juridical with secondary data, which is analyzed qualitatively then presented descriptively. The results of this study show that the process of political party cadre formation is not running well, such that political parties face difficulties approaching the election because there are no party cadres who have the competence and quality to be ready to compete in legislative elections, presidential and vice presidential elections, and regional head elections. Therefore, political parties must prepare a cadre formation program by preparing a curriculum that serves as a guideline in the cadre formation process in order to obtain competent, qualified, and integrated cadres.They are the ones who will be recruited to be nominated or included in political contests through general elections and regional head elections to become legislative members, presidents and vice presidents, and regional heads and deputy regional heads. Good cadreship and recruitment will produce good leaders.